Expression for the base of the triangle: Let the height of the triangle be h. According to the given information, the base is four less than three times the height. Therefore, the expression for the base of the triangle would be 3h - 4.
Equation for the area of the triangle, substituting in for the base: The formula for the area of a triangle is A = (1/2)bh, where A is the area, b is the base, and h is the height. Substituting the expression for the base into the formula, we get A = (1/2)(3h - 4)(h).
The first step in solving for h: Start by substituting the given value of the area (38 cm^2) into the equation: 38 = (1/2)(3h - 4)(h).
From here, one can solve this quadratic equation for h using various methods such as factoring, completing the square, or using the quadratic formula.
19. The base of a triangle is four less than three times the height. The area of the triangle is 38 square centimeters. A=(b×h)2
An expression for the base of the triangle:
Equation for the area of the triangle, substituting in for the base:
The first step in solving for h:
3 answers
20. Solve the equation for y: 3x+5y=60
(1 point)
Responses
y=57x5
y is equal to 57 x over 5
y=−35x+12
y is equal to negative 3 fifths x plus 12
y=60+3x5
y is equal to 60 plus 3 x over 5
y=60−3x
(1 point)
Responses
y=57x5
y is equal to 57 x over 5
y=−35x+12
y is equal to negative 3 fifths x plus 12
y=60+3x5
y is equal to 60 plus 3 x over 5
y=60−3x
To solve for y in the equation 3x + 5y = 60, we can rearrange the equation to isolate y.
Here are the steps:
1. Start with the equation 3x + 5y = 60.
2. Subtract 3x from both sides of the equation to isolate y:
3x + 5y - 3x = 60 - 3x
Simplify the equation:
5y = 60 - 3x
3. Divide both sides of the equation by 5 to solve for y:
y = (60 - 3x) / 5
So, the solution for y is y = (60 - 3x) / 5.
Here are the steps:
1. Start with the equation 3x + 5y = 60.
2. Subtract 3x from both sides of the equation to isolate y:
3x + 5y - 3x = 60 - 3x
Simplify the equation:
5y = 60 - 3x
3. Divide both sides of the equation by 5 to solve for y:
y = (60 - 3x) / 5
So, the solution for y is y = (60 - 3x) / 5.